Leadership Beyond the Schoolhouse: Preparing Principals to Engage in Advocacy (in Ethridge et al.'s "Advocacy in Education: Research-Based Strategies for Teachers, Administrators, and Teacher Educators") - Trombly, Christopher (2020)
Advocacy has become a crucial professional obligation for school principals. Seen by policymakers as honest brokers who have at heart the best interests of the children and families whom they serve, school principals should offer themselves to policymakers and their staffs as accessible and reliable sources of information about the actual or likely impacts of measures that have already been enacted or that are being introduced. They should be ready to collect, examine, and articulate data of interest to policymakers. Moreover, they should provide compelling stories for those policymakers to remember and retell as they debate, not only education-specific measures, but any policies impacting children’s ability to be healthy, safe, engaged, supported, and challenged.
Keywords: dept.edl